1989
DOI: 10.1111/j.1365-2672.1989.tb04569.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ethanol content of beer on the heat resistance of a spoilage Lactobacillus

Abstract: D‐values of a heterofermentative beer spoilage lactobacillus were measured at 55°C, 60°C and 65°C in beers containing <0·05% to 4·4% v/v ethanol. Z‐values for the different beers varied between 9·17 and 12·13°C. At each temperature an increase in ethanol reduced the measured D‐value. The maximum, 5·01 min was observed in alcohol‐free beer (<0·05%) at 55°C and the minimum, 0·31 min, at 60°C and 65°C in beer containing 4·4% ethanol. D‐values could be increased by prior growth in the presence of ethanol. They cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Some researchers could not isolate certain species of Lactobacillus during alcoholic fermentation though the species were detected before fermentation (Lafon-Lafourcade et al, 1983), probably due to low ethanol tolerance. Although some strains of L. jwctivoruns have a high tolerance to ethanol and can be a problem in dessert wines (Fornachon et al, 1949, Vaughn et al, 1949, some strains of this species including WS-14C apparently lack this characteristic (Adams et al, 1989).…”
Section: -Journalmentioning
confidence: 99%
“…Some researchers could not isolate certain species of Lactobacillus during alcoholic fermentation though the species were detected before fermentation (Lafon-Lafourcade et al, 1983), probably due to low ethanol tolerance. Although some strains of L. jwctivoruns have a high tolerance to ethanol and can be a problem in dessert wines (Fornachon et al, 1949, Vaughn et al, 1949, some strains of this species including WS-14C apparently lack this characteristic (Adams et al, 1989).…”
Section: -Journalmentioning
confidence: 99%
“…However, data from a previously performed study at Campden BRI demonstrated considerably lower D 60 values of 0.06-0.10 min for a strain of L. brevis (unpublished observations). Studies conducted by Adams et al (19) highlighted the impact of the chemical environment on microbial thermo tolerance, particularly the beverage pH and ethanol concentration, with other chemical factors also likely to play a significant role. The present study assessed the growth and thermo tolerance of common beer and brewery related spoilage organisms in two beer styles.…”
Section: Introductionmentioning
confidence: 99%
“…Heat destruction tests applied in practice had in common the fact that the death rate coefficient (specific death rate) (k) or the decimal reduction time (D) were determined at different temperatures in several experiments (Lundt, 1951;Wucherpfennig and Franke, 1968;Roth, 1969;Djien et al, 1972;Jacobs et al, 1973;Put et al, 1976;Senhaji and Loncin, 1977;Splittstoesser and Splittstoesser, 1977;Merkel and Perry, 1977;Juven et al, 1978;Rajan et al, 1978;Adams et al, 1989).…”
Section: Introductionmentioning
confidence: 99%